MG-112 Ten new cases further delineate the syndromic intellectual disability phenotype caused by mutations in DYRK1A. (4th December 2015) - Bronicki, Lucas; Redin, Claire; Drunat, Severine; Piton, Amélie; Lyons, Michael; Passemard, Sandrine; Baumann, Clarisse; Faivre, Laurence; Thevenon, Julien; Rivière, Jean-Baptiste; Isidor, Bertrand; Gan, Grace; et al.
Abstract : Background: The dual-specificity tyrosine phosphorylation-regulated kinase 1A (DYRK1A) gene on chromosome 21q22.13 within the Down syndrome critical region has been implicated in syndromic intellectual disability associated with Down syndrome and autism. DYRK1A plays a critical role in brain growth and development primarily by regulating cell proliferation, neurogenesis, neuronal plasticity and survival. Several patients with chromosome 21 aberrations, such as partial monosomy, involving multiple genes including DYRK1A have been reported. In addition, seven other individuals have been described with chromosomal rearrangements, intragenic deletions or truncating mutations that specifically disrupt DYRK1A. Most of these patients have microcephaly and all have significant intellectual disability. Objectives: The purpose of this study was to further delineate the recurrent clinical features and types of mutations that disrupt DYRK1A in patients with 'DYRK1A syndrome'. Design/method: Targeted or whole exome next-generation sequencing and array comparative genomic hybridization analysis were used to identify DNA sequence variations and copy number variants, respectively. Results: We identified unique mutations in DYRK1A in nine patients and a large chromosomal deletion that encompassed DYRK1A in one patient. These individuals had a recurrent pattern of clinical manifestations including primary or acquired microcephaly, intellectual disability ranging from mild to severe, speech delay or absence, seizures, autism, motor delay, deep-set eyes, poor feeding and poor weight gain. Conclusions: Based on the increasing identification of mutations in DYRK1A, we suggest this gene be considered as potentially causative in patients presenting with intellectual disability, primary or acquired microcephaly, feeding problems and absent or delayed speech with or without seizures.